2018
DOI: 10.1002/ijfe.1613
|View full text |Cite
|
Sign up to set email alerts
|

Testing for nonlinear unit roots in the presence of a structural break with an application to the qualified PPP during the 1997 Asian financial crisis

Abstract: This paper applies Monte Carlo simulations to evaluate the size and power properties in the presence of a structural break, for the standard Augmented Dickey‐Fuller (ADF) test versus nonlinear exponential smooth transition autoregressive unit root tests. The break causes the tests to be undersized, and the statistical power considerably decreases. Moreover, the effect is intensified in small samples and very much increased for more persistent nonlinear series. As a remedy, we modify the standard ADF and expone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Many studies also argue for investigating nonlinearity and structural break simultaneously for PPP because they are not mutually exclusive (Sollis, 2004;Christopoulos & León-Ledesma, 2010;Omay et al, 2018Omay et al, , 2020Nazlioglu et al, 2022) 7 Nonlinear unit root test of Kapetanios et al (2003) has been very popular among researchers and an increasing number of studies are devoted to test PPP using this testing procedure. Erlat (2004); Liew et al (2004); Bahmani-Oskooee et al (2007; Ozdemir (2008); Wu and Lee (2008); ; ; Telatar and Hasanov (2009); Su et al (2014); Yildirim (2017); Habimana et al (2018) are some of these studies, among others. But Choi and Moh (2007) argue that this test has serious problems in practice on large power loss and the source of this power loss is unknown and Li and Park (2018) For OECD countries, several studies are using various unit root tests, and the fastgrowing empirical methodology of unit root testing has also influenced the findings of these studies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many studies also argue for investigating nonlinearity and structural break simultaneously for PPP because they are not mutually exclusive (Sollis, 2004;Christopoulos & León-Ledesma, 2010;Omay et al, 2018Omay et al, , 2020Nazlioglu et al, 2022) 7 Nonlinear unit root test of Kapetanios et al (2003) has been very popular among researchers and an increasing number of studies are devoted to test PPP using this testing procedure. Erlat (2004); Liew et al (2004); Bahmani-Oskooee et al (2007; Ozdemir (2008); Wu and Lee (2008); ; ; Telatar and Hasanov (2009); Su et al (2014); Yildirim (2017); Habimana et al (2018) are some of these studies, among others. But Choi and Moh (2007) argue that this test has serious problems in practice on large power loss and the source of this power loss is unknown and Li and Park (2018) For OECD countries, several studies are using various unit root tests, and the fastgrowing empirical methodology of unit root testing has also influenced the findings of these studies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As an alternative to ADF and PP tests, BBC unit root test is also executed following the study of Pippenger and Goering [66]. Literature findings demonstrate that nonlinear unit root tests outperform their linear counterparts in terms of size and power properties [67,68]. Those studies suggest using nonlinear models since the standard unit root tests might yield misleading results in the presence of nonlinear dynamics.…”
Section: Empirical Analysismentioning
confidence: 99%
“…For instance, the results of Yavuz and Yilanci 14 showed that per capita CO 2 emissions of G7 countries are converging until reaching a threshold value but diverging after this value. As pointed out by Habimana et al., 15 the power of the nonlinear unit root tests, as well as the linear ones, are reduced if there are structural changes in the data generation process because nonlinear models are incapable of capturing changes. Therefore, it is necessary to use a unit root test that allows for both multiple smooth changes and nonlinearities in the series.…”
Section: Introductionmentioning
confidence: 99%